Antiviral therapies for managing viral hepatitis in lymphoma patients. (4th March 2017) - Merli, Michele; Rattotti, Sara; Gotti, Manuel; Arcaini, Luca
ABSTRACT: Introduction : In patients with lymphoma the detection of positive hepatitis B or C viruses (HBV and HCV) serology involves crucial therapeutic consequences. In HBV-infected patients the serological profile of active (HBsAg-positive) or resolved (HBsAg-negative/anti-HBcAb-positive) infection is associated to differential risk of viral reactivation during rituximab-based therapy and require appropriate strategies of monitoring and of antiviral prophylaxis. In HCV-associated NHL patients consolidated data demonstrated that interferon (IFN)-based antiviral therapy (AT) is able to induce lymphoma regression strictly related to viral eradication, while preliminary data of the new direct-acting antivirals (DAAs) are very promising. Areas covered : This review summarizes current evidences about HBV reactivation risk in patients undergoing rituximab-based treatments and appropriate options of antiviral prophylaxis with lamivudine, entecavir or tenofovir, as well as pre-emptive strategy in HBsAg-negative/HBcAb-positive patients. Moreover previous experiences with IFN-based AT as well as recent studies with DAAs in HCV-associated indolent lymphomas or diffuse large B-cell lymphoma (DLBCL) are reviewed. Expert opinion : Entecavir or tenofovir prophylaxis is recommended for HBsAg-positive patients, while universal prophilaxis with lamivudine may be preferred in HBsAg-negative/anti-HBc-positive patients. In asymptomatic patients with HCV-associated indolent lymphoma DAA-based AT should be used as first-line option, while in DLBCL its deliver after immunochemotherapy-induced complete remission is suggested.